Drug regulation of microRNA - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2023)
The scientific review provides the mechanisms of drug regulation of microRNA in the human body. To write the article, information was searched using Scopus, Web of Science, MEDLINE, PubMed, Google Scholar, Embase, Global Health, The Cochrane Library databases. To restore the reduced functional activity of microRNAs, replacement therapy is used, with modified synthetic analogs of endogenous microRNAs, and drugs that enhance the production of the body's own microRNAs. The authors state that numerous studies have confirmed the effectiveness of miRNA replacement therapy. It is known that there are several groups of drugs among miRNA inhibitors: anti-miRNA oligonucleotides, miRNA traps, miRNA mimics that prevent miRNA binding; peptide nucleic acids, small-molecule inhibitors. The authors suggest that the expression of drug-metabolizing enzymes is controlled by nuclear receptors and transcription factors, epigenetic regulation such as DNA methylation and histone acetylation, and post-translational modification. It is emphasized that ursodeoxycholic acid modulates the expression of some miRNAs. It is known that probiotic bacteria can modulate the expression level of miRNA genes. The use of probiotics is accompanied by a change in the expression of numerous genes of the body involved in the regulation of the inflammatory response, allergic reactions, metabolism and other biological processes. Thus, modern science is intensively studying the potential of using drugs that restore miRNA content or inhibit miRNA activity for the therapy of miRNA-dependent conditions. The results of scientific research confirmed the therapeutic effect of ursodeoxycholic acid and probiotic preparations due to the effect on the activity of miRNA generation in hepatobiliary diseases. Therefore, the introduction into clinical practice of drugs than can modulate the content and expression of specific miRNAs will certainly open new perspectives in the treatment of patients with hepatobiliary diseases.